Sistem Pendukung Keputusan Pemilihan Bibit Jagung Unggulan Pada Desa Gumuk Rejo Menggunakan Metode (SAW) - Azhari, Amalyanda; Priyangan, Donny Muda (Publikasi Indonesia, 2021)
Corn Seed is a very popular commodity plant planted by farmers especially Indonesia because many people use this plant in addition to its many benefits it is also a food crop. Users usually have difficulty choosing Corn Seeds to be bought because of the many types of Corn Seeds, soil construction, and prices. So we need a decision support system that can help users determine the Corn Seed according to the desired alternatives and criteria. In this study, the method used is Simple Additive Weighting (SAW), providing information and assisting farmers in making decisions about the superior corn seedlings they will use. Corn seeds are very important for us because corn seeds are the main factor and determinant of the success of farmers in Gumuk Rejo village. In making the decision support system application selection of superior corn aunt uses the PHP programming language and uses the MySql database.